EFFECT OF TEMPERATURE ON THE DEVELOPMENT OF Oligota centralis Sharp (COLEOPTERA: STAPHYLINIDAE), PREDATOR OF TETRANIQUID MITES ON YUCCA Manihot esculenta Crantz - LENIS-C., JORGE IVÁN; BELLOTII, ANTHONY; ZULUAGA-C., JOSÉ IVÁN; MESA-C., NORA CRISTINA; CRISTINA-DUQUE, MYRIAM (Revista Colombiana de Entomología, 1989)
Staphylinidae beetles are predators of Tetranychidae mites. On cassava, Manihot esculenta Crantz two species, belonging to genus Oligota, have been found: O. minuta and O. centralis being the first one predominant and the object of this study. O. centralis has been recorded preying upon the casava green mite Mononychellus progresivus and two-sppoted spider mite Tetranychus urticae in various regions of tropical America. Experiments were established under laboratory conditions at four temperatures (15, 20, 25 and 30°C) and 70+ 50/o R.H. to study developmental time, minimum developmental threshold, and physiological time for O. centralis. Additionally, the effect of the two prey, M. progresivus and T. urticae, on the egg to adult development was studied. The predator showed three larval instars and total developmental time from egg to adult of 58,9, 31,9, 18,9, and 16,4 days at 15, 20, 25, and 30°C respectively. The egg stage, first, second, and third instar larvae and pupae required 76,9; 19,6; 27,3; 28,6 y 166,32 degree-days to complete development. The minimum developmental threshold was 7,3, 12, 1,3,7, 9,2, and 9,8°C for each stage. The egg-to-adult duration was 18,9 days when preying on T. urticae and 18,2 days on M. progresivus.